2021
DOI: 10.3390/ani12010094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Litter Size and Parity on Farrowing Duration of Landrace × Yorkshire Sows

Abstract: Litter size has increased and farrowing duration has also prolonged in recent years. The aim of this study was to analyze the effect of litter size and parity on farrowing duration (FAR) to estimate the possibility of selecting a short farrowing duration. We recorded 32,200 parturitions of 8420 Landrace × Yorkshire sows, determined farrowing duration, litter size, parity, gestation length. Results showed that total number of born (TNB) and parity obeyed a cubic (p = 0.0004, p = 0.004) relationship while number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…Oliviero et al [ 6 ] reported that the average duration of farrowing in modern swine production can range from 156 to 262 min, and farrowing lasting more than 300 min should be considered prolonged farrowing. Likewise, Ju et al [ 7 ] suggested that a farrowing duration of 240 to 300 min can be considered the ideal cutoff point for Landrace x Yorkshire hybrid sows in a commercial pig farm having 5 to 22 TB. Prolonged farrowing duration can cause postpartum complications in sows and increase the percentage of stillborn piglets per litter (SB) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oliviero et al [ 6 ] reported that the average duration of farrowing in modern swine production can range from 156 to 262 min, and farrowing lasting more than 300 min should be considered prolonged farrowing. Likewise, Ju et al [ 7 ] suggested that a farrowing duration of 240 to 300 min can be considered the ideal cutoff point for Landrace x Yorkshire hybrid sows in a commercial pig farm having 5 to 22 TB. Prolonged farrowing duration can cause postpartum complications in sows and increase the percentage of stillborn piglets per litter (SB) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Putting gilts (parity 1) aside, several authors provide evidence to suggest there is no significant interaction between the parity of a sow and the duration of farrowing [ 26 , 29 , 100 ]. Contrastingly, others contest this and present evidence to support farrowing duration increasing alongside sow parity [ 101 , 102 , 103 , 104 ]. Ju et al [ 102 ] suggest this could be due to the aging of the uterine muscle tissue after multiple farrowings, reducing the ability to contract, and hence, prolonging the parturient process.…”
Section: Factors Affecting Parturitionmentioning
confidence: 85%
“…Contrastingly, others contest this and present evidence to support farrowing duration increasing alongside sow parity [ 101 , 102 , 103 , 104 ]. Ju et al [ 102 ] suggest this could be due to the aging of the uterine muscle tissue after multiple farrowings, reducing the ability to contract, and hence, prolonging the parturient process. It was also shown that factors such as litter size, body condition and environment are highly correlated with parturition success and determining the effect of parity alone is difficult [ 102 ].…”
Section: Factors Affecting Parturitionmentioning
confidence: 85%
See 1 more Smart Citation
“…It is also important to note that these sows started farrowing later in the day and thus there would have been a prolonged period between their last feed and onset of farrowing. Based on the subset of data and previous research ( Feyera et al, 2018 ; Gourley et al, 2020 ; Ju et al, 2021 ), it is possible that these sows had longer farrowing durations and were associated with increased stillborn. Interestingly, when the interaction of treatment and farrowing duration is considered in the subset, it was seen that two feeds did decrease stillborn rate in shorter farrowing sows.…”
Section: Discussionmentioning
confidence: 99%